Gold 20
Jump to navigation
Jump to search
Generalized hypergeometric function
- Gold ID
- 20
- Link
- https://sigir21.wmflabs.org/wiki/Generalized_hypergeometric_function#math.70.58
- Formula
- TeX Source
{}_1F_0(1;;z) = \sum_{n \geqslant 0} z^n = (1-z)^{-1}
Translation Results | ||
---|---|---|
Semantic LaTeX | Mathematica Translation | Maple Translations |
Semantic LaTeX
- Translation
{}_1 \AppellF{0}(1 ; ; z) = \sum_{n \geqslant 0} z^n =(1 - z)^{-1}
- Expected (Gold Entry)
\genhyperF{1}{0}@{1}{}{z} = \sum_{n \geqslant 0} z^n = (1-z)^{-1}
Mathematica
- Translation
- Expected (Gold Entry)
HypergeometricPFQ[{1}, {}, z] == Sum[(z)^(n), {n, 0, Infinity}] == (1 - z)^(- 1)
Maple
- Translation
- Expected (Gold Entry)
hypergeom([1], [], z) = sum((z)^(n), n = 0..infinity) = (1 - z)^(- 1)